SAT0439 Ultrasensitive Detection of Calcium Crystals in Synovial Fluid of Patients with Knee Osteoarthritis. Relation with Clinical, Instrumental, Laboratory Assessment in Different Phases of Disease. (10th June 2014) - Frallonardo, P.; Oliviero, F.; Peruzzo, L.; Lorenzin, M.; Ortolan, A.; Punzi, L.; Ramonda, R.
Abstract : Background: Osteoarthritis (OA) is characterized by a progressive loss of articular cartilage, osteophyte formation, thickening of the subchondral bone, along with frequent signs of intraarticular inflammation with moderate synovitis (1). The role of inflammation in the pathogenesis of OA especially in its early phases is becoming increasingly evident (2). The role of calcium crystals (CC) in synovial inflammation and their significance in OA progression in this context continues to be debatable (3). Objectives: The aim of this study was to evaluate the presence of CC in synovial fluid (SF) using ultrasensitive analysis with scanning electron microscopy (SEM) at early and later stages of symptomatic and radiographic knee OA (KOA). Methods: Seventy-four consecutive outpatients with KOA, 35 (47.3%) of whose were in an early stage (<1 year), underwent arthrocentesis of the knee. SF samples were examined under compensated polarized light microscopy and SEM. Patients' medical history, clinical features, Kellgren Lawrence radiological score (KL) X-ray findings depending on, ultrasound power Doppler (PD) signal were assessed. The Western Ontario and McMaster Universities OA Index (WOMAC) self-assessment questionnaire, the Lequesne algofunctional index (Lequesne) survey, and the visual analogic scale forms were assessed in all patients. All gave written informed consent. Results: CC were detected by SEM in SF in 35.1% of the patients; a higher polymorphonuclear (PMN) percentage was found in these patients with respect to those without CC. On the basis of disease duration, the patients were subdivided into three groups (A <1 yr; B 1-5 yrs; C >5 yrs). In group A, patients with CC had a higher number of SF WBC and percentage of PMN than those without. No significant findings were identified in groups B and C. PD resulted positive in 43.24% of all the patients, 62.5% of these were CC + by SEM. When KL I-II were compared to KL III-IV patients, a significant difference was found with regard to: disease duration (35.79±54.13 vs 82.19±74.90; p=0.0017), disability (929.19±218.47 vs 1117.35±259.11; p=0.0272), WOMAC total index (1244.69±302.82 vs 1362.46±338.53; p=0.0584) and the Lequesne index (8.60±2.46 vs 9.81±2.48; p=0.0367). PD positivity was significant in the patients with CC + KL I and II with respect to those without CC- (p<0.0006). Conclusions: The sensitive SEM method used permitted us to identify CC+ in SF which were associated with an increased degree of joint inflammation (WBC and PMN) in early KOA. PD detected local inflammation in 62.5% of the patients with CC. Curiously, the PD decreased about 30%, in group C patients with CC. These data lead us to hypothesize that in patients with a longer disease duration the CC + have less pro-inflammatory properties. These results suggest that CC, which may be crucial in the early phase of OA pathogenesis, may play a role in inducing inflammatory reactions. References: Scanzello CR, Goldring SR. The role of synovitis in osteoarthritis pathogenesis. Bone. 2012;51:249-57 2. Berenbaum F. Osteoarthritis as an inflammatory disease (osteoarthritis is not osteoarthrosis!) Osteoarthritis Cartilage. 2013;21:16-21. Rosenthal AK. Crystals, inflammation, and osteoarthritis. Curr Opin Rheumatol. 2011;23:170-3. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5956